2016
DOI: 10.1080/87565641.2016.1194840
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Mechanisms of Auditory Information Processing in Adolescence: A Study on Sex Differences

Abstract: To date, little is known about sex differences in the neurophysiological correlates underlying auditory information processing. In the present study, auditory evoked potentials were evoked in typically developing male (n = 15) and female (n = 14) adolescents (13-18 years) during an auditory oddball task. Girls compared to boys displayed lower N100 and P300 amplitudes to targets. Larger N100 amplitudes in adolescent boys might indicate higher neural sensitivity to changes of incoming auditory information. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As to why the current effect was specifically observed in women is not entirely clear. Some sex differences have been reported ( Bakos et al, 2016 , Nanova et al, 2008 ), but a recent systematic review showed that the effect of sex on P300 latency is minimal to none ( Melynyte et al, 2018 ). Also, sex specific concerns in the presentation of ADHD may be considered ( Nussbaum, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…As to why the current effect was specifically observed in women is not entirely clear. Some sex differences have been reported ( Bakos et al, 2016 , Nanova et al, 2008 ), but a recent systematic review showed that the effect of sex on P300 latency is minimal to none ( Melynyte et al, 2018 ). Also, sex specific concerns in the presentation of ADHD may be considered ( Nussbaum, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of only 13 children in each group of this study potentially obscures any more subtle relationships between the mismatch effect and SES. In fact, developmental auditory oddball studies often have smaller sample sizes and/or group designs that potentially limit sensitivity, for example: Korpilahti et al (2001) N=10, Lovio et al (2009 N=17, Cao et al (2008) N=12 per group, Bakos et al (2016) N=14 and N=15 in each group, Orinstein and Stevens (2014) N=18 and N=20 in each group.…”
Section: Introductionmentioning
confidence: 99%
“…(2009) N = 17, Cao et al. (2008) N = 12 per group, Bakos et al. (2016) N = 14 and N = 15 in each group, and Orinstein and Stevens (2014) N = 18 and N = 20 in each group.…”
Section: Introductionmentioning
confidence: 99%